Cultivation and cryopreservation of Dientamoeba fragilis xenic cultures in RPMI medium - Kyrychenko, Igor; Biriukov, Mykhailo; Pokhil, Sеrgiy; Tymchenko, Olena (Problems of Cryobiology and Cryomedicine, 2025)
Dientamoeba fragilis is one of the most common intestinal protozoan parasites in humans and many animals, which can cause acute and chronic lesions of the gastrointestinal tract. Growing and preservation of D. fragilis cultures in vitro allows studying the features of the life cycle of these parasites, their pathogenic potential, sensitivity to antimicrobial drugs, etc. In this work, the suitability of RPMI nutrient medium for in vitro cultivation and cryopreservation of xenic cultures of D. fragilis was studied for the first time. Based on the results of sowing fresh fecal samples from Ukrainian military personnel (with confirmed monoinvasion of D. fragilis) in RPMI (with 10% heat-inactivated horse serum, without antibiotics), it was established that RPMI is quite suitable for growing both short-term and long-term xenic cultures of D. fragilis. Growth profiles on RPMI (at 37 °C in microaerophilic conditions) of different isolates of D. fragilis are similar. D. fragilis cultures grown on RPMI are highly suitable for studying the morphological structure of these protozoa cells, their division processes, the formation of pseudopodia, pre-cysts and cysts. The most effective cryopreservation of D. fragilis trophozoites is achieved in a composition based on RPMI containing DMSO in a final concentration of 7.0%. The smallest trophozoites (12—15 μm) are the most resistant to freezing and ensure the recovery of growth of D. fragilis cultures after their cryopreservation. Probl Cryobiol Cryomed 2025; 35(1):33–45